Preservative Effects on Crude Bromelain Stability and Enzymatic Applications - Jiyapa Sripirom; Watcharin Chumjan; Wanitcha Rachadech; Kantima Sripajan; Jirada Sena-art (Brazilian Archives of Biology and Technology)
Abstract Agricultural waste management is a critical environmental and economic issue. Thailand is one of the world's leading pineapple growers. Pineapples contain bromelain, a very important protease. This study used an ammonium sulfate precipitation method to partially purify bromelain from pineapple peel waste, which represented the largest enzyme portion with the highest level of specificity. The study findings indicate that partially purified bromelain is more stable and has nearly twice the activity of crude bromelain. Based on SDS-PAGE analysis, bromelain has a molecular weight of approximately 24 kDa. The enzyme’s stability was assessed in the presence and absence of preservatives. The preservatives, chitosan and sodium benzoate, both reduced bromelain activity and affected the protein pattern as well as the brightness of clear zones analyzed using SDS-PAGE. Using chitosan instead of sodium benzoate results in a less decreased bromelain activity. Dehairing tests showed unwinding of hairs and gentle scraping without visible collagen destruction, suggesting proper skin peeling upon closer examination. The enzyme completely removes stains from cloth samples. These results indicate that the enzyme can aid hair and stain removal. Leather and washing applications may benefit from the use of crude bromelain. Since enzymes naturally degrade, it would be advisable to add appropriate preservatives.